Kajian Strategi Peningkatan Keselamatan Pelayaran Kapal-Kapal Tradisional - Malisan, Johny; Jinca, M Yamin (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
Construction and shipbuilding of traditional ships are individual character, and should be preserved. Traditional ships are generally managed by middle economic groups of people, but very strategic in distributing public goods to the islands that are difficult for conventional vessels. Problem that emerged in traditional ships is high level of accidents and caused predominantly by their human resources. Therefore, in this research attempted strategies to overcome the problem through SWOT analysis in order to improve safety performance of traditonal ships. Result of analysis showed the need some strategies among others capacity building of human resource in shipbuilding, to encourage the improvement of shipbuilding standards, to encourage the improvement of ship classification standards, and to encourage their ability in mastery of loading and unloading systems.